2009
DOI: 10.1016/j.ejcts.2008.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Use of N-acetylcysteine to reduce post-cardiothoracic surgery complications: a meta-analysis

Abstract: Post-cardiothoracic surgery (CTS) complications (e.g. myocardial injury, renal dysfunction, atrial fibrillation) may occur as a result of enhanced systemic inflammation, perhaps provoked by an oxidative stress response. N-acetylcysteine (NAC) is a free radical scavenger antioxidant agent that may attenuate this physiologic response and reduce post-CTS complications. Thus, a meta-analysis was performed to help characterize the potential beneficial effects of perioperative NAC administration in patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…The cardioprotective efficacy of NAC in cardiac surgery has been reported in a number of recent studies [24][25][26] . However, a considerable number of studies have concluded that the use of NAC in cardiac surgery did not appear to bestow any statistically significant benefits [27,28] . In a study by Bapat et al [29] intended to determine survival and evaluate quality of life after 1 year in patients with prolonged ICU stays after cardiac surgery utilizing CABG, it was estimated that 1-year mortality in patients with prolonged ICU stays after cardiac surgery remains high.…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotective efficacy of NAC in cardiac surgery has been reported in a number of recent studies [24][25][26] . However, a considerable number of studies have concluded that the use of NAC in cardiac surgery did not appear to bestow any statistically significant benefits [27,28] . In a study by Bapat et al [29] intended to determine survival and evaluate quality of life after 1 year in patients with prolonged ICU stays after cardiac surgery utilizing CABG, it was estimated that 1-year mortality in patients with prolonged ICU stays after cardiac surgery remains high.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized study including 115 patients undergoing CABG or valve surgery, Ozaydin et al [46] demonstrated that NAC markedly reduces the incidence of POAF lasting more than 5 minutes. A previous meta-analysis [47] evaluated potential beneficial effects of perioperative NAC on the prevention of complications after cardiothoracic surgery. In the sub-group analysis of six trials which reported POAF as study endpoints, the use of NAC significantly lowered the risk of developing POAF by 36%.…”
Section: N-acetylcysteinementioning
confidence: 99%
“…Acta Pharmacologica Sinica npg metal toxicity, and psychiatric disorders [24][25][26][27] . Several studies have shown that NAC could be used for the treatment of pulmonary fibrosis, liver fibrosis, and skin fibrosis [28][29][30][31] .…”
Section: Wwwchinapharcom Shen Y Et Almentioning
confidence: 99%